2014
DOI: 10.3892/ol.2014.2703
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous occurrence of gastrointestinal stromal tumor and intrahepatic cholangiocarcinoma: A case report

Abstract: Various cases of gastrointestinal stromal tumor (GIST) coinciding with other gastrointestinal malignancies have been reported to date, however, the synchronous occurrence of GIST and intrahepatic cholangiocarcinoma (ICC) is exceptionally rare and, to the best of our knowledge, has only been reported once. The coinciding malignancy has usually been encountered incidentally during surgical exploration. Thus, this is the first report where a targeted biopsy of the clinically suspicious lesion was used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…ICC occasionally coexists with other cancers, such as lymphoma, [5] renal cell carcinoma, [6] hepatocellular carcinoma, [79] thyroid cancer, [10] and gastrointestinal stromal tumors. [11] Only 2 reports are available in the literature about colorectal metastases with ICC; however, both diagnoses were delayed. [3,4]…”
Section: Discussionmentioning
confidence: 99%
“…ICC occasionally coexists with other cancers, such as lymphoma, [5] renal cell carcinoma, [6] hepatocellular carcinoma, [79] thyroid cancer, [10] and gastrointestinal stromal tumors. [11] Only 2 reports are available in the literature about colorectal metastases with ICC; however, both diagnoses were delayed. [3,4]…”
Section: Discussionmentioning
confidence: 99%
“…Nam et al reported a case of advanced synchronous GIST and ICC, which was operable at initial presentation, but progressed to become surgically unresectable [9]. They concluded that the possibility of multiple primary tumors must be considered as an alternative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous cancers are defined as those where secondary tumors occur simultaneously or within 6 months of diagnosis of the primary malignancy [ 4 ]. ICC sometimes coexists with other cancers such as HCC [ 5 8 ], GIST [ 9 , 10 ], thyroid cancer [ 11 ], lymphoma [ 12 ], and renal cell carcinoma [ 13 ]. Only one case with synchronous double cancer consisting of combined HCC-ICC and metastasis of a colon adenocarcinoma, which were treated by curable resection, has been reported [ 1 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation